(untitled) (Global Scientific Review, 2022)
Dear reader, this article provides information about the drugs used in heart failure, one of the diseases that are currently common ingangj . For most people, Heart Failure is a long-term condition that cannot be treated. But treatment can help keep symptoms under control, possibly for many years. The main treatment options are: healthy lifestyle changes, medications, devices installed on your chest to control heart rhythm, surgery. In most cases, a combination of treatment is required.